ANTIOXIDANT ACTIVITES AND PHYTOCHEMICAL ANALYSIS OF METHANOL EXTRACT OF LEAVES OF ARTOCARPUS HETEROPHYLLUS LAM - Raaman, N.; Sivaraj, C.; Tenzing (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The aim of the present investigation was to evaluate the phytochemical constituents, free radical scavenging activities and antioxidant properties of the methanol extract of leaves of Artocarpus heterophyllus. Methods: The phytochemicals in the methanol extract of leaves of A. heterophyllus were determined qualitatively and quantitatively using standard methods. The antioxidant activities were carried out by DPPH free radical scavenging assay, OH• radical scavenging assay, NO• radical scavenging assay, Fe3+reducing power assay and phosphomolybdenum reduction assay methods. Results: The methanol extract of leaves of A. heterophyllus showed good radical scavenging activities and reducing power activities which were found to increase with the increasing concentration of the extract. The study indicated that the presence of the major phytochemicals viz. flavonoids and phenols in the methanol extract of leaves of A. heterophyllus were 86.75 mg/g and 524.86 mg/g, respectively. Conclusion: The present study revealed that the methanol extract of leaves of A. heterophyllus showed significant antioxidant activities as well as phenolic content.